Vivência da sexualidade a partir do relato de pessoas com deficiência intelectual - Maia, Ana Cláudia Bortolozzi [UNESP] (Universidade Estadual de Maringa, 2016)
This qualitative descriptive study investigated the experience of sexuality and sexual health from reports of 12 people, men and women, with intellectual disabilities who participated in an interview. The participants showed difficulties in verbalizing concepts about sexuality, but were capable of expressing it without any aloofness or weirdness. They report the occurrence of dating, usually without sex and guarded by adults; when reported, the intercourse occurs in places of little privacy and often withou t condoms. There are those who covet marriage and reproduction, but also those who postpone or avoid maternity / paternity, revealing choices about their reproductive lives. Due to superficial information provided by an ineffective sex education and taking on affective and sexual lives, they are found in vulnerable conditions. We conclude that the sexuality of people with intellectual disabilities is quite similar to that of other people when referring to the expression of erotic desire and exposure to social standards; this population should receive sex education that contributes to the full exercise of their sexuality and to the respect of their sexual rights.
Sexuality experience as from report of people with intellectual disability
Keywords: Intellectual disability; Sex education; Sexuality